Building Academic and Spiritual Excellence at Al-Noori Muslim School Australia: a Holistic Approach - Isma Nur Hanifa; Umi Robi’atin Musfa’ah (IAI Al Muhammad Cepu, 2025)
This research examines the implementation of an Islamic value-based holistic education approach at Al-Noori Muslim School, Australia, as a model for integrating academic, spiritual, and social excellence. Employing a qualitative method with content analysis, this study investigates curriculum documents, school policies, and various pedagogical practices to understand how Islamic values are integrated into modern education. The findings indicate that Al-Noori Muslim School successfully harmonizes the Australian Curriculum with Islamic teachings through integrated learning in subjects such as Business Studies, Economics, and Arabic, as well as through spiritual experiences like Umrah programs, religious camps, and the habitual practice of Islamic values in daily activities. Learning support programs further reflect Islamic values of inclusivity and compassion. However, the implementation of this holistic model faces challenges, including the pressure of national academic standards, limitations in teacher competency regarding value integration, and the need to maintain a balance between academic and spiritual demands. Strategies employed to address these issues include teacher professional development, cross-curricular collaboration, experiential learning, and integrated assessments encompassing both academic and character (akhlak) aspects. This study concludes that an Islamic value-based holistic approach is capable of nurturing students into insan kamil (the perfect human)—individuals who are knowledgeable, faithful, and of noble character. Furthermore, this model serves as a reference for other Islamic schools in navigating the challenges of modern education without compromising Islamic principles.